Is fair trade “fair”? : a study of handmade paper producers in Nepal - Kharel, Arjun (Kansas State University, 2011)
The label “fair-trade” might seem to be a definitive designation: either a product is or isn’t. In fact, a continuum exists, resultant mostly from the participation in fair-trade by diverse groups of producer organizations, buyers, certifying organizations, and consumers. Therefore, the way fair-trade is perceived and practiced cannot be presumed to be homogenous. In order to better understand the complexities of fair-trade, a qualitative study was carried out to examine one fair-trade product and its producers. Two Nepalese handmade paper companies, Bhaktapur Craft Paper (BCP) and Get Paper Industry (GPI), were studied to gain insight into the producers’ perceptions, interpretations, and practices of fair-trade. This study also assesses the impact of fair-trade affiliation on the socio-economic conditions of producers and workers. To provide the opportunity for comparison, the cases of BCP and GPI were also compared, where possible, to those of a non-fair-trade company, Bagmati Paper Industries (BPI). The study finds that the fair-trade producer organizations were affiliated with fair-trade networks primarily to promote their business by way of the multiple and committed trading partners involved in fair-trade. Also, affiliation seemed to have positive impacts on the overall business of the paper companies, contributing to growth in sales over the years. Likewise, different training programs sponsored by fair-trade organizations, such as Fair Trade Group Nepal and World Fair Trade Organization-Asia, and fair-trade buyers also contributed to the capacity enhancement of producer organizations. The producers in the paper companies lacked an understanding of fair-trade due to a lack of participation in decision making, a high level of illiteracy among producers, and because management did not consider producer awareness of fair-trade as significant. The study finds positive impacts of fair-trade involvement on the producers’ socio-economic position: a company’s participation in and practice of fair-trade is positively related to improvement in the socio-economic conditions of producers. Considering wages, work-hours, working conditions, and job satisfaction of workers, the fair-trade companies were determined to more favorably affect workers’ lives than the non-fair-trade company.
Keywords: Fair Trade; Development; Handmade paper; Nepal; International development; Sociology (0626)